Petra. Od nabatejskiego centrum do bizantyjskich peryferii - Szubert, Barbara (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2013)
The reviewed article is devoted to the history of the city of Petra from the first century BC, when it was the capital city of the Nabataean people, up until the sixth century, when it found itself on the borderlands of the Byzantine empire.
Keywords: Petra; Nabataeans; ancient pre-islamic Arabia; Roman empire; Byzantine empire